Strength and performance asymmetry during maximal velocity sprint running - Exell, T.; Irwin, G.; Gittoes, M.; Kerwin, D. (Scandinavian Journal of Medicine & Science in Sports, 2017)
The aim of this study was to empirically examine the interaction of athlete-specific kinematic kinetic and strength asymmetry in sprint running. Bilateral ground reaction force and kinematic data were collected during maximal velocity (mean = 9.05 m/s) sprinting for eight athletes. Bilateral ground reaction force data were also collected while the same athletes performed maximal effort squat jumps. Using novel composite asymmetry scores, interactions between kinematic and kinetic asymmetry were compared for the group of sprinters. Asymmetry was greater for kinematic variables than step characteristics, with largest respective values of 6.68% and 1.68%. Kinetic variables contained the largest asymmetry values, peaking at >90%. Asymmetry was present in all kinematic and kinetic variables analyzed during sprint trials. However, individual athlete asymmetry profiles were reported for sprint and jump trials. Athletes' sprint performance was not related to their overall asymmetry. Positive relationships were found between asymmetry in ankle work during sprint running and peak vertical force (r = 0.895) and power (r = 0.761) during jump trials, suggesting that the ankle joint may be key in regulating asymmetry in sprinting and highlighting the individual nature of asymmetry. The individual athlete asymmetry profiles and lack of relationship between asymmetry of limb strength and sprint performance suggest that athletes are not "limb dominant" and that strength imbalances are joint and task specific. Compensatory kinetic mechanisms may serve to reduce the effects of strength or biological asymmetry on the performance outcome of step velocity.